الليزينغ في الفقه الإسلامي الشركة الوطنية للإيجار المالي أنموذجا - علي, شيخه بلقاسم (جامعة الوادي university of eloued, 2023)
" يتناول البحث موضوع الليزينغ في الفقه الإسلامي، من خلال نموذج عقد الشركة الوطنية للإيجار المالي، وتكمن إشكاليته في مدى تحقيق هذا الأخير لشروط الإجارة المنتهية بالتمليك وضوابطها. وقد تضمّن البحث مبحثين: خصصنا المبحث الأول لعرض حقيقة الليزينغ وبيان حكمه، بينما المبحث الثاني فقد اشتمل على دراسة فقهية لعقد الشركة الوطنية للإيجار المالي، فبدأناه بتعريف هذا العقد ثمّ تطرقنا إلى التكييف الفقهي له من خلال دراسة أهم المسائل فيه، منها غرامة التأخير واشتراط الأمين التجاري، وتحميل المستأجر جميع مصاريف الصيانة، وضمان العين المستأجرة. وقد توصلنا في الأخير إلى أنّ عقد الشركة الوطنية للإيجار المالي وإن كان ابتدأ لا يختلف عن الإجارة المنتهية ويتوافق معها في كونه اجارة تنتهي بعقد بيع مستقل عن عقد الإجارة، إلاّ أنّه يحوي خللا كبيرا لاشتراطه الغرامة التأخيرية والعمل بالتأمين التجاري، وتضمين المستأجر للعين المستأجرة، ولذلك كان توصياتنا العمل على تعديل هذا العقد بما يوافق الشريعة، التي يحرص أغلب الناس على التعامل وفق مبادئها. ""Our research deals, infact with geasing in Islamic jurisprudence taking as an example The National Financial Leasing Company. Our research issue consists in finding out whether the former company achives the conditions of the lease ending in ownership or not. Our research includes two topics, the first deals with showing leasing reality and its legality, where as the second cosists of jurisprudential study of the National Financial Leasing Company contract. At first we started with the definition of this contract then we moved to jurisprudential adaptation through studing its most important disorders such as the problem of late tax, commercial assurance requirment charging tenant all expenses of mintenance as well as rexled objects warranty. In the end, we are find out that although the NFLC contract does not differ from the leasing ending in ownership since both lead to leasing ending in an independent sale from rent contract, it includes some defects through requiring late tax and commercial assurance. Thêtas why one of our recomendations was the modefication of this contract according to Islamic laws that most of people prefer dealing according to its principles. "
شريعة
Keywords: الليزينغ، الإجارة المنتهية بالتمليك، غرامة التأخير، الضمان.; leasing, lease ending in ownership, late tax, warranty.